Kajian Keberagaman Genetik Nyamuk Anopheles barbirostris dan A. vagus di dua Daerah Endemik Penyakit Malaria di Jawa Barat - R. Ameria Sumatri; Djoko T. Iskandar (Institut Teknologi Bandung, 2005)
Genetic diversity of two mosquitoes species in two malaria endemic areas, Tasikmalaya and Pelabuhan Ratu, has been studied using isozyme techniques on cellulose acetate gels. Fifteen enzyme systems have been analyzed for this study, performed on 46 specimens of Anopheles vagus and 44 specimens of A. barbirostris, each representing both study areas. Polymorphism in A. vagus was lower (P= 0.20-0.27) compared to A. barbirostris (P= 0.40-0.47) and the heterozigosity level of A. vagus (H = 0.027-0.031) was equally lower compared to A. barbirostris (H= 0.083-0.100) in both populations. Numerous diagnostic alleles representing each populations and species were found, but each of them only occurred at very low frequencies. These results clearly showed that the two areas were distinct entities and not as part of two related meta-populations. Unfortunately such results have a very low applicable advantage to study the population genetics of the two species or populations. One gene, Pgm owns a number of diagnostic alleles characteristics for each population at a relatively high frequencies, but its advantages are negligible, because their frequencies do not follow the Hardy-Weinberg equation, This phenomenon could be explained by: (1) unequal gene frequencies between sexes caused by gender; (2) hidden species or (3) low number of analyzed individuals and (4) artifact of electrophoresis techniques. The Tasikmalaya populations for the two distinct species had a lower genetic diversity compared to Pelabuhan Ratu populations. These results were interpreted as follows: Tasikmalaya populations suffered from human activities and had more or less uniform habitats or in the other hand, Pelabuhan Ratu populations were much larger than those from Tasikmalaya. The results of Pelabuhan Ratu were more variable as a logical consequence of having a more extensive population with more Anopheles species as the area included forested and garden or plantation areas but less rice-fields and had likely undergone lesser exposure to human activities.